Integrative analysis of microRNA-320a-related genes in osteoarthritis cartilage - Peng, Hao; Lin, Haibin (Frontiers in Surgery, 2023)
Objectives To investigate microRNA-320a-related differentially expressed genes (DEGs) and pathways in osteoarthritis (OA) by bioinformatic analysis. Methods The target genes of microRNA-320a were searched and collected from MiRTarBase microRNA Targets dataset, the TargetScan Predicted Nonconserved microRNA Targets dataset and the TargetScan Predicted Conserved microRNA Targets dataset. OA-related microRNAs and OA-related target genes were collected from GeneCards databases. The pathway enrichment analysis of miRNAs ware performed by Funrich analysis tool. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis was obtained from Database for Annotation, Visualization and Integrated Discovery (DAVID). GeneMANIA and STRING are used for protein-protein interaction (PPI) network analysis. Module analysis was performed by Cytoscape. Results A total of 176 OA related miRNAs were searched and collected for enrichment analysis, and microRNA-320a was one of OA related miRNAs. Enrichment pathway and analysis of 1721 miRNA-320a-related target genes from MiRTarBase and TargetScan were performed using the online tools Metascape. And results shown that the biological processes were remarkably enriched in chromatin organization, cellular response to DNA damage stimuli, mRNA metabolic process, protein ubiquitination, and regulation of cell adhesion. And then we analysed miRNA-320a-targeted OA genes via KEGG, GO enrichment and PPI Network. Our results showed that miRNA-320a played a role in OA through FoxO signaling pathway, PI3K-Akt signaling pathway, focal adhesion, MAPK signaling pathway, HIF-1 signaling pathway and cellular senescence. And we speculate that MAPK signaling pathway plays a key role in the effect of miRNA-320a on OA. Conclusion This study implied microRNA-320a-related DEGs and dysregulated pathways in OA. The aim is to screen miRNA-320a-related genes and pathways in OA and, eventually, to improve the understanding of underlying mechanisms of miRNA-320a in OA.